Changes in Food Consumption and the Implications for Food Security and undernourishment: India in the 1990s - Ranjan Ray (Development and Change 38(2): 321-343 (2007)., 2007)
This article examines the changes in the nature and quantity of food consumption in India during the reform decade of the 1990s, and analyses their implications for calorie intake and undernourishment. The study documents the decline in cereal consumption, especially in the urban areas, and provides evidence that suggests an increase in the prevalence of undernourishment over the period 1987/88 to 2001/2002. The results also point to a significant number of households, even in the top Expenditure decile, suffering from undernourishment. This calls for a reassessment of the current strategy of directing the Targetted Public Distribution System (TPDS) exclusively at households `below the poverty line'. This study shows that, both as a source of subsidized calories and as a poverty reducing instrument, the PDS is of much greater importance to female-headed households than it is to the rest of the population. Another important result is that, notwithstanding the sharp decline in their expenditure share during the 1990s, rice andwheat continue to provide the dominant share of calories, especially for the rural poor. The overall message is that, especially in a period of significant economic change, one needs to go beyond the standard expenditure-based money metric measures to assess the changes in the living standards of households.